DAMPAK INTEGRASI BATALYON AZOV KEDALAM GARDA NASIONAL UKRAINA TERHADAP HUBUNGAN UKRAINA-RUSIA - Paranggi, Dimas Umbu Landu; Saeri, Mhd. (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This research identifies the impact of the integration of the Azov battalion into the Ukrainian national guard on Ukrainian-Russian relations. The research is interesting to discuss because the development of the relationship situation between Ukraine and Russia, which is now in a state of war, has been affected by the existence of the Azov battalion and the integration of the Azov battalion into the national guard. This research is a qualitative research with data collected through library research technique. The theory used is the theory of constructivism. This research uses the nation state level of analysis where state behavior can be dictated by internal factors of the state. The results of this study show that the integration of the Azov battalion into the Ukrainian national guard and then the political involvement of actors associated with the Azov battalion such as the Azov movement is used as a weapon in Russian propaganda to accuse the Ukrainian government of being fascist, terrorist and genocidal in its efforts to delegitimize the Ukrainian state government. This propaganda is then used by Russia as justification for its casus belli that there needs to be a